Birthweight and gestational age‐specific neonatal mortality rate in tertiary care facilities in Eastern Central Uganda - Mubiri, Paul (Health Sci Rep, 2020)
BACKGROUND: An estimated 2.8 million neonatal deaths occur each year globally, which accounts for at least 45% of deaths in children aged less than 5 years. Birthweight and gestational age‐specific mortality estimates are limited in low‐resource countries like Uganda. A deeper analysis of mortality by birthweight and gestational age is critical in identifying the cause and potential solutions to decrease neonatal mortality. OBJECTIVES: We studied mortality before discharge in relation to birthweight and gestational age using a large sample size from selected tertiary care facilities in Uganda. METHODS: We used secondary data from the East Africa Preterm Birth Initiative study conducted in six tertiary care facilities. Birth records of infants born between October 2016 and March 2019 with a gestational age greater than or equal to 24 weeks and/or birthweight greater than or equal to 500 g were reviewed for inclusion in the analysis. Newborn death before discharge was the outcome variable of interest. Multivariable Poisson regression modeling was used to explore birthweight and gestational age‐specific mortality rate. RESULTS: We analysed 50 278 birth records. Among these 95.3% (47 913) were live births and 4.8% (2365) were stillbirths. Of the 47 913 live births, 50% (24 147) were males. Overall, pre‐discharge mortality was 13.0 per 1000 live births. For each 1 kg increase in birthweight, mortality before discharge decreased by −0.016. As birthweight increases, the mortality before discharge decreased from 336 per 1000 live births among infants born between 500 and 999 g, to 4.7 per 1000 live births among infants born weighing 3500 to 3999 g, and increased again to 11.2 per 1000 live births among infants weighing more than 4500 g. CONCLUSIONS: Our study highlights the need for further research to understand newborn survival across different birthweight and gestational categories.